TEACHERS’ STRATEGY TO IMPROVE STUDENTS’ RELIGIOUS CHARACTER THROUGH READING YAASIIN HABITUATION AT SDN SIMPANG TIGA CILEGON - Nining Roihatul Jannah; Ujang Jamaludin; Istinganatul Ngulwiyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the teachers’ strategy to improve students’ religious character through reading Yaasiin habituation in Grade VA at SDN Simpang Tiga. The method used in this research was qualitative, with a descriptive qualitative approach. Data were collected through observation and interviews, and then analyzed using the Miles and Huberman model. The results of this study revealed that Islamic education teachers at SDN Simpang Tiga improved students’ religious character through the habituation of reading Yaasiin. It was found that the teachers were able to carry out the process of improving students’ religious character through distance learning activities and identify the religious character possessed by Grade VA students at SDN Simpang Tiga.